Studi Profil Desainer, Konsep, dan Karya Art Furniture (Studi Kasus: Barata Sena) - Rosalina Fanny Samantha; Yusita Kusumarini; Lucky Basuki (Intra, 2018)
This research aims to interpret datas related to the profile study of Barata Sena who is a designer of furniture art. Wood is a fundamental material for Barata Sena's creative process. Woods that tend to be neglected by logging or woodworking fields such as hollowed, moldy, cracked, and curved woods are considered as a defect. For Barata Sena, that is not a problem. Everything born by Mother of Earth is natural things because in his creative thinking, whatever flaws of the trees, the problem is just how to integrate his intelligence into his cooperation with those tree trunks. The basic problems in this research are how the complete profile and philosophy in producing artwork furniture of Barata Sena and how the embodiment process of Barata Sena’s furniture artwork. The author uses qualitative descriptive method by doing in-depth interviews with the designer and documentation related on the field datas, such as masterpieces photos, interview result of Barata Sena with Bulan Soerbadjati, and internet source about Barata Sena. The design method used by Barata Sena is adjacent to the biomimicry design method, which inspiration comes from nature. The result of this study identifies the complete profile of Barata Sena and reveals Barata Sena's philosophy in his work and the process of it. In the process based on the main philosophy that